2015
DOI: 10.1016/j.zool.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Current directions and future perspectives from the third Nematostella research conference

Abstract: The third Nematostella vectensis Research Conference took place in December 2013 in Eilat, Israel, as a satellite to the 8th International Conference on Coelenterate Biology. The starlet sea anemone, N. vectensis, has emerged as a powerful cnidarian model, in large part due to the extensive genomic and transcriptomic resources and molecular approaches that are becoming available for Nematostella, which were the focus of several presentations. In addition, research was presented highlighting the broader utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The precise mechanisms by which mesenteries are formed during embryonic and larval development are poorly described. A first report proposes that these structures are formed by a combination of the pharyngeal ectoderm and body wall endoderm (Aman and Technau, unpublished in [ 46 ]). These observations suggest that in the regenerating polyp resulting from adult physa isolation, the mesenteries form in a similar way to those that form during embryonic development, from the already formed pharynx (the origin of which is unclear) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms by which mesenteries are formed during embryonic and larval development are poorly described. A first report proposes that these structures are formed by a combination of the pharyngeal ectoderm and body wall endoderm (Aman and Technau, unpublished in [ 46 ]). These observations suggest that in the regenerating polyp resulting from adult physa isolation, the mesenteries form in a similar way to those that form during embryonic development, from the already formed pharynx (the origin of which is unclear) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to traditional terrestrial models (e.g., Drosophila and Caenorhabditis elegans ), aquatic animals are amendable to both field and laboratory experiments. A rising aquatic model species in the fields of evolutionary ecology and genomics is the estuarine cnidarian Nematostella vectensis (Darling et al, 2005 ; Tarrant et al, 2015 ). Recent studies using laboratory populations have shown that the microbial diversity associated with N. vectensis individuals is influenced significantly by developmental stage, temperature, and salinity, as well as the geographic location from which individuals were collected, despite ten years of laboratory culture (Mortzfeld et al, 2015 ).…”
Section: Toward Nature's Laboratorymentioning
confidence: 99%
“…The starlet sea anemone, Nematostella vectensis , has emerged as a powerful cnidarian model with a sequenced genome and a growing suite of available molecular resources and tools 11 12 . Nematostella is widely distributed in brackish environments and unsurpassed for the ease with which its entire life cycle is maintained in the laboratory 13 14 .…”
mentioning
confidence: 99%